STRATEGI BAURAN PRODUK IKONIK UMKM ALOEVERA DI KOTA PONTIANAK - Nurcholifah, Ita (Jurnal Keuangan dan Perbankan Syariah, 2020)
One of the areas and cities that have natural resources is the city of Pontianak. These natural resources are in the form of aloe vera (Aloe vera). Aloe vera is a plant that is easy to grow on peatlands in the city of Pontianak and has high benefits and economic value. So that this plant can be used as various types of food and beverage processing. The development of MSMEs in Pontianak City, of course, must be supported by an effort to keep the business running and progress in business, especially in terms of income, so that gradually the UMKM can "upgrade" to become a large and developing business so that it can support the very foundation of the national economy awaited by the Indonesian government. Therefore, this study aims to determine the iconic product strategy in the product width line, product length line, product depth line and MSME product consistency lines. This research uses a descriptive qualitative approach.The four dimensions of the product mix help the company in defining the company's product strategy, where the company can expand its business in four ways, the company can add to its product lines, namely: expanding its product mix, the company can extend each product line, the company can add product variations and deepen the mix. By implementing a product mix strategy with a four-dimensional approach, it is hoped that Aloevera MSMEs can develop more on an international or global scale. With the creation of more varied products based on the needs and desires of consumers.